A Commodity Frontier nos Cerrados: O complexo da soja nas Regiões de Planejamento de Goiás (1974-2019) - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The constitution of the soy complex in Goiás is a historical process triggered by the global “commoditization” movement of Glycine (L) Merr in the early 1970s. Based on this premise, this research sought to identify and systematize some historical conditions for the expansion of soybean frontier in Goiás, as well as their respective impacts on the configuration of the Planning Regions of Goiás in relation to the installed soybean complex. Our research suggests that commodity frontier soybeans were more induced in the Southwest Goiás Planning Region with 67% of its territory occupied by soybeans in 2019. The same induced agronomic development process occurred with less intensity and more oriented towards grassroots projects of technological innovation in the Planning Regions of Southeast Goiás (Railway) and Surroundings of the Federal District, resulting in 65% and 44% of their respective territories occupied by the soybean crop in 2019. The analyzes also indicate as conditioning factors of this process: a) the commodity frontier of soybeans and a context of international division of agricultural frontiers; b) an extensive list of developmental policies aimed at inducing and maintaining agro-industrial complexes; c) R&D-oriented international cooperation. Finally, the research tested and validated the hypothesis that in the commodity frontier of soybeans in Goiás, historically there was a phase oriented towards agroindustrialization aimed at the European market, followed by a reorientation of the productive forces towards the insourcing of soybeans aimed at the Chinese market. Based on the analyzed results, this research still makes notes and raises hypotheses.
Commodity Frontier in Cerrado: The soy complex in the Planinng Regions of Goiás ( 1974-2019)
Keywords: Economia mundial - Soja; Soja - Goiás(Estado); Soja - Commodity Frontier - Goiás; World Economy; Soya - Goiás(state); Soya - Commodity Frontier - Goiás(Estado); CIENCIAS SOCIAIS APLICADAS::ECONOMIA